Exploring collaborative scriptwriting and virtual drama performance: Enhancing English language education through technology integration - Rita Inderawati; Eryansyah Eryansyah; Machdalena Vianty; Zuraida Zuraida; Rita Hayati; Muthmainnah Muthmainnah; Ermalati Putri (Universitas Syiah Kuala, 2024)
The present study elaborates on the process of collaborative scriptwriting for drama and the implementation of virtual platforms for theatrical performances. The qualitative design approach was used to provide a detailed explanation of how the virtual drama performance about The Spread of Islam in the 16th Century by Ratu Bagus Kuning was rehearsed and recorded. The subject of the study was 18 graduate school students who took the Appreciation and Literature Teaching course in a Graduate School of English Education at a state university in Indonesia. The data obtained from observation, interview, and documentation were analyzed by utilizing a thematic process. The result of the study reveals two main findings: it emphasizes innovative scriptwriting and video presentation in virtual educational drama, and it also shows the communication, cooperation, critical thinking, and creativity involved in writing drama scripts and performing virtually. The study highlights the process of collaborative drama script writing, focusing on Palembangs heroic tale of Ratu Bagus Kuning. Using the universitys LMS for dialogues, research, and creative collaboration, students prepared for a virtual drama performance. They paired up to draft scenes, actively applying 21st-century skills, such as critical thinking and creativity. Peer feedback and revisions improved script quality. Despite continuity issues and technical constraints, students showed resilience and adaptability. Rehearsals and the final virtual performance demonstrated their dedication and innovation. The integration of technology and cultural sensitivity highlighted virtual dramas transformative potential, emphasizing communication, collaboration, critical thinking, and creativity.